2011
DOI: 10.1021/bi1019622
|View full text |Cite
|
Sign up to set email alerts
|

A Nanomolar-Potency Small Molecule Inhibitor of Regulator of G-Protein Signaling Proteins

Abstract: Regulators of G-Protein signaling (RGS) proteins are potent negative modulators of signal transduction through G-Protein coupled receptors. They function by binding to activated (GTP-bound) Gα subunits and accelerating the rate of GTP hydrolysis. Modulation of RGS activity by small molecules is an attractive mechanism to fine-tune GPCR signaling for therapeutic and research purposes. Here we describe the pharmacologic properties and mechanism of action of CCG-50014, the most potent small molecule RGS inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
125
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(135 citation statements)
references
References 30 publications
9
125
1
Order By: Relevance
“…Like CCG-4986, CCG-63802 showed selectivity for RGS4 over other RGS proteins studied. A third series of small molecule RGS4 inhibitors is represented by CCG-50014, which is the first RGS inhibitor that has shown activity in cells (Blazer et al, 2011). A derivative of CCG-50014, CCG-203769, was also demonstrated to have effects in vivo.…”
Section: Advances In Rgs Protein Drug Discovery -From Biochemical Actmentioning
confidence: 99%
“…Like CCG-4986, CCG-63802 showed selectivity for RGS4 over other RGS proteins studied. A third series of small molecule RGS4 inhibitors is represented by CCG-50014, which is the first RGS inhibitor that has shown activity in cells (Blazer et al, 2011). A derivative of CCG-50014, CCG-203769, was also demonstrated to have effects in vivo.…”
Section: Advances In Rgs Protein Drug Discovery -From Biochemical Actmentioning
confidence: 99%
“…Modulation of RGS proteins might alter GPCR signaling in a pathway-and tissue-specific manner (Blazer and Neubig, 2009). Although RGS proteins are considered to be difficult drug targets (Tesmer et al, 1997), we and others have made significant progress in developing RGS protein inhibitors (Roman et al, 2007;Blazer et al, 2010Blazer et al, , 2011Turner et al, 2012). In other cases, however, increasing RGS protein function may be therapeutically beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, we (Zhong and Neubig, 2001; and others (Doggrell, 2004;Riddle et al, 2005;da Costa Goncalves et al, 2008) suggested that RGS proteins, including RGS2, might represent novel cardiovascular therapeutic targets. Although significant progress has been made in identifying RGS inhibitors (Blazer et al, 2011;Turner et al, 2012), enhancing RGS action is more challenging .…”
mentioning
confidence: 99%
“…This idea has been bolstered by the intriguing phenotypes observed in mice carrying RGS-insensitive Ga mutants, which showed that blocking RGS actions potentiates neurotransmitter actions and linked behaviors in a targeted fashion (Talbot et al, 2010;Lamberts et al, 2013). While initial efforts focused on the identification and development of peptide inhibitors of RGS proteins as proof of concept (Jin et al, 2004;Wang et al, 2008), more recent work has focused on the development of small molecule inhibitors with the goal of treating multiple diseases, including neurologic disorders (Blazer et al, , 2011Roman and Traynor, 2011;Turner et al, 2012;Storaska et al, 2013). Thus far, RGS4 has been the main focus for the development of small molecule RGS inhibitors.…”
Section: Discussionmentioning
confidence: 99%